First-line pembrolizumab used concurrently with multi-agent chemotherapy and inhaled tranexamic acid (TXA) for management of stage III mixed trophoblastic tumor complicated by pulmonary hemorrhage - Rose Emlein; Heather Einstein; Amy Brown; Amanda Ramos; Jonathan A. Cosin; Clare Zhou; Marguerite Palisoul (Gynecologic Oncology Reports)
Introduction: We report a case of the use of nebulized TXA and first line pembrolizumab with chemotherapy for treatment of Stage III gestational trophoblastic neoplasia (GTN) in the setting of hemodynamic instability secondary to pulmonary hemorrhage. Case review: The patient is a 44 year old G3P2 with newly diagnosed Stage III intermediate trophoblastic tumor (epithelial trophoblastic tumor and placental site trophoblastic tumor) with known pulmonary metastases. She was admitted for anemia secondary to hemoptysis requiring blood transfusion and expedition of chemotherapy. She received induction etoposide & cisplatin (EP) and was initiated on nebulized tranexamic acid. After two cycles of induction chemotherapy with continued increase in β-hcg levels she was started on pembrolizumab in addition to first-line multi agent chemotherapy with etoposide, methotrexate, actinomycin-D (EMA)-EP. She received six cycles of EMA/EP with pembrolizumab, requiring various dose reductions and delays. β-hcg reached a maximum of 72,316 on cycle 1 day 1 of EMA/EP and normalized after cycle 3. She completed 12 months of maintenance pembrolizumab. Β-hcg has remained undetectable and she has recovered to her pre-diagnosis level of functioning. Conclusion: GTN can be highly vascular and pulmonary metastases can cause life-threatening hemorrhage. Nebulized TXA provides a promising method to stabilize pulmonary hemorrhage in GTN. Pembrolizumab has been previously shown to be effective in recurrent or chemo-resistant GTN. Use in combination with first line therapy in GTN provides a promising option for patients with highly morbid disease, requiring aggressive therapy.